Influence of environmental conditions on the temperature distribution in a pipe-embedded wall (with a thermally activated element) – analysis of the measurement results - Małek, Maria; Koczyk, Halina (Instal, 2023)
The article presents the influence of environmental conditions on the temperature distribution in a pipe-embedded wall. For this purpose, measurements were taken on a test stand, a concrete wall with thermoplastic pipes (with a thermally activated element) embedded inside it in its symmetry axis. The wall is insulated with polystyrene on both sides. Additionally, as a result of its closure in an insulated casing made of oriented strand board (OSB), 2 air zones were created on both sides of the wall. The concreted loop was connected to a cooling bath thermostat used to set the supply temperature in the pipes. In the case of air, its supply to the air zones was provided by ventilation ducts mounted to the housing. The tests consisted of two stages: stabilization of the temperature on the surface of the partition between the concrete and polystyrene layer and the reaction of the structure to a variable outside temperature when fresh outside air was supplied to one of the air zones. All measurements were performed for the following settings: 16°C, 18°C, 20°C and 22°C. It was notedthat in order to achieve an even temperature on the wall surface, 24 hours were required from the moment the cooling bath thermostat was turned on. When outside air is supplied to one of the air zones, this partition is resistant to temperature fluctuations, and only after about 6 hours a temperature change of 0.1°C takes place for sensors located at the extreme measurement points and in the other air zone (without air inflow).